Islamic Propagation Council of Indonesia (DDII) Preaching Management in Developing Islamic Society in Metro City - Rohman, Fathur; Achlami; Yanti, Fitri; Isnaeni, Ahmad (International Journal of Educational Research Excellence, 2025)
This study examines the management of the Islamic Propagation Council of Indonesia (DDII) in the context of developing an Islamic society in Metro. In the era of modernization, Islamic propagation organizations face challenges in re-examining their roles and functions, especially when dealing with complex political and social dynamics. As a structural Islamic propagation institution, DDII has a strategic position in shaping the order of Islamic life through the approach of Islamic propagation bi al-lisān and bi al-hāl. This study aims to analyze three main aspects: the concept of Islamic propagation of DDII, Islamic propagation management in developing Islamic society, and the implementation of the concept of developing Islamic society in Metro City. Using a qualitative approach with a single instrumental case study method, this study involved participant observations, in-depth interviews, and documentation analysis. Key informants included the leadership of DDII Metro City, senior figures of the organization, religious figures, and the local Muslim community. The results of the study indicate that DDII has developed an adaptive and inclusive Islamic propagation model with a focus on strengthening aqidah, empowering the economy of the community, and optimizing the role of the mosque. In the digital era, DDII responded to the challenges by developing digital da'wah infrastructure and improving the competence of da'i in the use of modern technology. Despite facing various challenges, including the shifting role of da'wah organizations in the context of contemporary politics, DDII managed to maintain its position as a moral force that contributed to the development of Islamic society and the integrity of the nation. This study provides theoretical contributions in the development of structural da'wah management and practical contributions for stakeholders in optimizing the role of da'wah for the development of Islamic society